The Effect of Mediation on Patient Satisfaction on the Relationship between Characteristics and Quality of Service on Patient Loyalty at the Beringin Jaya Public Health Center Labuhan Batu Selatan - Sri Astuti; Agus Seswandi; Helwen Heri (SAINS ORGANISASI, 2022)
This study aims to analyze the effect of patient characteristics and service quality and the mediating relationship of patient satisfaction on patient loyalty. Where this research was conducted at the Beringin Jaya Public Health Center. Sources of data from this study were employees at the Beringin Jaya Public Health Center Indonesia. With the number of respondents as many as 100 as the research sample. Furthermore, the data analysis techniques in the form of descriptive analysis, convergent and discriminant validity tests and reliability tests, and SEM-PLS analysis. Research results: from data that has been processed. Shows the calculation of patient characteristics has an effect on patient satisfaction, service quality has an effect on satisfaction, patient satisfaction has an effect on patient loyalty, patient characteristics negatively have no effect on patient loyalty, service quality has no negative effect on patient loyalty, patient satisfaction mediates patient characteristics on patient loyalty, Patient Satisfaction mediates Service Quality on Patient Loyalty.